2016
DOI: 10.1016/j.jtcvs.2016.04.068
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ring versus suture annuloplasty for tricuspid valve repair in patients undergoing mitral valve surgery

Abstract: Late survival and TV durability following concomitant TV repair during MV surgery did not differ with respect to TV repair technique. In this series of patients with repaired tricuspid valves, etiology of MV disease did not influence postoperative changes in TR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
2
34
0
1
Order By: Relevance
“…More than 80% of TR encountered in clinical practice is secondary or functional in nature. FTR usually results from left-sided heart disease, most often MV stenosis or regurgitation (16). The common mechanism of FTR is annular dilatation and leaflet tethering.…”
Section: Mortality and Follow Upmentioning
confidence: 99%
“…More than 80% of TR encountered in clinical practice is secondary or functional in nature. FTR usually results from left-sided heart disease, most often MV stenosis or regurgitation (16). The common mechanism of FTR is annular dilatation and leaflet tethering.…”
Section: Mortality and Follow Upmentioning
confidence: 99%
“…20 Systolic pulmonary artery pressure (sPAP) was estimated by continuous-wave Doppler of the TR jet using the modified Bernoulli equation and right atrial pressure, which was estimated according to inferior vena cava size. 10 The indications for TAP included grade 3 or 4 TR and/or pulmonary hypertension (sPAP >50 mmHg) and/or TV annular dilatation (>21 mm/m 2 ) and/or symptomatic right heart failure (HF).…”
Section: Methodsmentioning
confidence: 99%
“…10 Several studies have demonstrated the superiority of ring annuloplasty over suture annuloplasty. 11-15 However, others have supported suture annuloplasty, pointing out its predominance or the shortcomings of ring annuloplasty, such as moderate to severe TR remaining in approximately 10% of patients after TAP using prosthetic rings, 9 an increased risk of early ring dehiscence after the use of a rigid ring, 16,17 and the satisfactory early and long-term outcomes of suture annuloplasty.…”
mentioning
confidence: 99%
“…Nema razlike u preživljenju bolesnika, kasnijemu funkcijskom statusu, progresiji TR-a ili reoperaciji trikuspidnog zalistka između spomenutih dviju metode na temelju nedavnoga retrospektivnog ispitivanja. 28 Obje tehnike pokazuju dobre rezultate. Anuloplastika postavljanjem šavova brža je i jeftinija metoda.…”
unclassified
“…No difference in patient survival, late functional status, progression of TR or tricuspid valve reoperations has been found in a recent retrospective study comparing patients treated with suture annuloplasty and those submitted to ring annuloplasty. 28 Both techniques have been shown to yield good results. Suture annuloplasty can be performed easily and rapidly with a lower cost compared with ring annuloplasty which requires a commercially available prosthetic device.…”
mentioning
confidence: 99%